Internal and external drivers of green export business strategy: their impact on competitive advantage and performance - Leonidou, Leonidas C.; Katsikeas, Constantine S.; Fotiades, Thomas A.; Christodoulides, Paul (My University, 2012)
With the intensification of problems relating to the environment, exporting firms are increasingly confronted with ecologically conscious consumers and stricter environmental laws in many countries. The paper presents the results of a study conducted among 216 Greek exporters of manufactured goods, focusing on the internal and external drivers of an eco-friendly exporting business strategy, and its resulting effects on competitive advantage and performance. Our findings confirmed the instrumental role of environmental public concern, competitive intensity, organizational culture, and management profile on an eco-friendly export business strategy. The latter was found to have a positive effect on the firm’s product differentiation competitive advantage, although there was no impact on cost leadership advantage. The product differentiation advantage was in turn revealed to be positively associated with both export market performance and export financial performance. However, such association with performance was not established in the case of cost leadership advantage. Keywords
Keywords: Exporting; Environmental management; Business strategy; Business performance